Jordan : First Review Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criteria, Modification of Performance Criteria, and Rephasing of Access-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Jordan. (IMF Staff Country Reports; Country Report ;, 2013)
Fiscal consolidation, additional reserve buildup, and higher growth are key program objectives for the Jordanian authorities. Despite the socially difficult elimination of the fuel subsidy, program performance was mixed. Initiatives to strengthen banking supervision and develop capital markets are important. The program addresses economic imbalances and safeguards social stability. Executive Directors are satisfied with the action taken to rebuild reserves through an increase in interest rates and by attracting donor funds, as well as domestic dollar-denominated financing. The government is committed to working on steps to boost revenue.